(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Khongthawie S, Hasin S, Ponpinij S, Pinkaew N. 2023. Ground-dwelling ant diversity in forests and agricultural land use at Sakaerat Biosphere Reserve, Thailand. Biodiversitas 24: 5937-5946. Ants play essential roles in terrestrial ecosystems, for example, soil engineers, seed dispersers, biological control agents, and indicators to monitor environmental stress and disturbance. This research aimed to study the diversity and community composition of ground-dwelling ants at Sakaerat Biosphere Reserve and its surrounding areas. Pitfall traps collected ground-dwelling ants from three habitat types: agricultural areas, dry dipterocarp forests, and dry evergreen forests; the environmental factor in this work was soil temperature. The results revealed that 109 ant species in 40 genera belonging to 8 subfamilies. Notably, the dry dipterocarp forest exhibited the highest ant diversity with 71 species, followed by the dry evergreen forest and agricultural area with 62 and 54 species, respectively. Overall, the present study reveals that soil temperature and vegetation significantly influenced ant species composition; ant species being more likely to be found in forests than in agricultural areas, and species classified as uncommon groups based on occurrence were the largest group in every study site. Besides, the information on ant species obtained from this work had the potential to be used as bioindicator species for ecosystem management and human impacts on forests.